2015
DOI: 10.1038/srep14099
|View full text |Cite|
|
Sign up to set email alerts
|

Modulation of AMPA receptor mediated current by nicotinic acetylcholine receptor in layer I neurons of rat prefrontal cortex

Abstract: Layer I neurons in the prefrontal cortex (PFC) exhibit extensive synaptic connections with deep layer neurons, implying their important role in the neural circuit. Study demonstrates that activation of nicotinic acetylcholine receptors (nAChRs) increases excitatory neurotransmission in this layer. Here we found that nicotine selectively increased the amplitude of AMPA receptor (AMPAR)-mediated current and AMPA/NMDA ratio, while without effect on NMDA receptor-mediated current. The augmentation of AMPAR current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…Also, Coogan et al [79] demonstrated that in addition to the high-frequency stimulation-induced LTP, ERK1/2 inhibitor PD98059 prevented LTP induced by the application of the metabotropic glutamate receptor (mGluR) agonist (S)-dihydrophenylglycine (S-DHPG) and the K+ channel blocker tetraethylammonium chloride (TEA-LTP). Moreover, there is evidence showing that LTP-induction through high frequency stimulation in CA1 region of the hippocampus activates ERK in an NMDA receptor activation-dependent manner [81]. These results draw a clear link between ERK1/2 activation and hippocampal LTP, demonstrating a critical regulatory role for ERK1/2 in hippocampal plasticity.…”
Section: Effects Of Nicotine On Hippocampal Kinases and Transcriptionmentioning
confidence: 69%
See 2 more Smart Citations
“…Also, Coogan et al [79] demonstrated that in addition to the high-frequency stimulation-induced LTP, ERK1/2 inhibitor PD98059 prevented LTP induced by the application of the metabotropic glutamate receptor (mGluR) agonist (S)-dihydrophenylglycine (S-DHPG) and the K+ channel blocker tetraethylammonium chloride (TEA-LTP). Moreover, there is evidence showing that LTP-induction through high frequency stimulation in CA1 region of the hippocampus activates ERK in an NMDA receptor activation-dependent manner [81]. These results draw a clear link between ERK1/2 activation and hippocampal LTP, demonstrating a critical regulatory role for ERK1/2 in hippocampal plasticity.…”
Section: Effects Of Nicotine On Hippocampal Kinases and Transcriptionmentioning
confidence: 69%
“…In addition, nicotine increased AMPA/NMDA receptor ratio in the ventral tegmental area dopaminergic neurons [80]. Also, recently, Tang et al [81] found that nicotine increased AMPAR-mediated current amplitude in the prefrontal cortex and this effect was reversed by an α7-nAChR antagonist methyllycaconitine (MLA). This is similar to results from Mitsushima et al [82]that found that α7-nAChR antagonism blocked learning-related CA1 synaptic plasticity.…”
Section: Effects Of Nicotine On Hippocampus-dependent Learning and Mementioning
confidence: 99%
See 1 more Smart Citation
“…; Tang et al . ). Both of these processes are dependent on Ca 2+ influx and involve interaction with several other postsynaptic proteins.…”
Section: Discussionmentioning
confidence: 97%
“…Slices were cut at 2°C in a solution containing the following: 26 mM NaHCO 3 , 22 mM sucrose, 11 mM glucose, 1 mM NaH 2 PO 4 , 3 mM KCl, 0.5 mM CaCl 2 , and 7 mM MgCl 2 saturated with 95% O 2 and 5% CO 2 . Slices recovered for 1 h at room temperature in artificial cerebral spinal fluid (ACSF) (pH 7.4): 1.25 mM NaH 2 PO 4 , 124 mM NaCl, 3 mM KCl, 26 mM NaHCO 3 , 2.5 mM CaCl 2 , 10 mM glucose, and 1.3 mM MgCl 2 , saturated with 95% O 2 and 5% CO 2 (Tang et al, 2015). …”
Section: Methodsmentioning
confidence: 99%